ENERGY-SAVING MODES OF THE HEAT TREATMENT OF CONCRETE - Raximov, Akmalxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The precast concrete industry is one of the largest consumers of energy among other sectors of the national economy. Heat treatment is an integral and at the same time the longest and most energy-intensive process of precast concrete production. In this regard, based on the determination of optimal steaming modes in a hot climate, it will lead to savings in energy costs, which is the purpose of this study.